Les sympathies musculaires du brouillard : Bachelard, Debussy et les sources de l’imagination motrice - Spampinato, Francesco (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2024)
One of the deepest aspects of the human imagination lies in its carnal, embodied dimension, rooted in a moving body, a material, physical body, traversed by the forces and tensions, the pleasures and pains of life. We will begin by examining Gaston Bachelard’s understanding of this corporeal and gestural aspect of the imaginary. We will continue by examining the imaginary of bodily movement in the music of Claude Debussy, a composer whose aesthetic lends itself to an analysis inspired by Bachelardian principles. Listening to the piano prelude Brouillards engages the imagination by awakening the the listener’s “muscular sympathies”, “tonalized” by dreamlike landscape. An analysis of the images that emerge from the reception of this piece will then take us back to the origins of the human imagination.